The impact of intrinsic and extrinsic factors on the job satisfaction of dentists - Götz, Katja; Campbell, Stephen; Szecsenyi, Joachim (Community dentistry and oral epidemiology, 2012)
The Two-Factor Theory of job satisfaction distinguishes between intrinsic-motivation (i.e. recognition, responsibility) and extrinsic-hygiene (i.e. job security, salary, working conditions) factors. The presence of intrinsic-motivation facilitates higher satisfaction and performance, whereas the absences of extrinsic factors help mitigate against dissatisfaction. The consideration of these factors and their impact on dentists’ job satisfaction is essential for the recruitment and retention of dentists. Objectives The objective of the study is to assess the level of job satisfaction of German dentists and the factors that are associated with it. Methods This cross-sectional study was based on a job satisfaction survey. Data were collected from 147 dentists working in 106 dental practices. Job satisfaction was measured with the 10-item Warr-Cook-Wall job satisfaction scale. Organizational characteristics were measured with two items. Linear regression analyses were performed in which each of the nine items of the job satisfaction scale (excluding overall satisfaction) were handled as dependent variables. A stepwise linear regression analysis was performed with overall job satisfaction as the dependent outcome variable, the nine items of job satisfaction and the two items of organizational characteristics controlled for age and gender as predictors. Results The response rate was 95.0%. Dentists were satisfied with ‘freedom of working method’ and mostly dissatisfied with their ‘income’. Both variables are extrinsic factors. The regression analyses identified five items that were significantly associated with each item of the job satisfaction scale: ‘age’, ‘mean weekly working time’, ‘period in the practice’, ‘number of dentist's assistant’ and ‘working atmosphere’. Within the stepwise linear regression analysis the intrinsic factor ‘opportunity to use abilities’ (β = 0.687) showed the highest score of explained variance (R2 = 0.468) regarding overall job satisfaction. Conclusions With respect to the Two-Factor Theory of job satisfaction both components, intrinsic and extrinsic, are essential for dentists but the presence of intrinsic motivating factors like the opportunity to use abilities has most positive impact on job satisfaction. The findings of this study will be helpful for further activities to improve the working conditions of dentists and to ensure quality of care.